Living in India - Green Jen (London; Franklin Watts, 2019)
Welcome to India! In this book, young people tell you all about what makes their country special, from its great capital city, to the landscape, people, food and things to see and do. This series introduces readers aged 6 and up to different continents and countries around the world, highlighting the differences and similarities between them. Clear, friendly text and big photos make these books a great starting point for learning about geography in general, and countries in particular
Keywords: Juvenile works